The Effectiveness of Rewarding Through The Economic Token Method to Improve Discipline Early Children (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the effectiveness of giving rewards through the Economic Token Method in improving early childhood discipline. The methodology in this research uses descriptive quantitative, while this research method uses classroom action research. The subjects in this study were early childhood children at PAUD Nurul Jannah Kedaung Pamulang, South Tangerang, with a total of 32 students consisting of 16 male students and 16 female students. Collecting data using test instruments and observation sheets, data analysis techniques with simple statistics. The action research is provided by the teacher through collaboration between the teacher and the researcher. There are several stages that are commonly passed, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of this study indicate that the discipline of early childhood through the provision of rewards integrated with the token method increases in each cycle. In cycle II (two) there were 2 meetings, namely: at the 2nd meeting, 83% were in the very good category. The method applied is one alternative to get serious attention both from the institution and from the teacher. Efforts and efforts are needed on the part of educational institutions, in order to improve the discipline of early childhood by revising the learning plans that are tailored to the needs of students. Keywords: Giving rewards, economic token, early childhood discipline